Perancangan Aplikasi Similarity Deteksi Kemiripan Judul Disertasi Berbasis Web - Mayola, Liga; Hafizh, Muhammad; Putra, Deri Marse (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Education has a good goal and system, namely creating a generation that is trustworthy in its actions and scientific writing. An educated person must have ethics in writing work, one of which is avoiding plagiarism. Determining the title of the dissertation that will be submitted must pay attention to several aspects to avoid similarities or even the same title because taking someone's writing or ideas without citing the source is an action that is prohibited in the ethics of scientific work. To prevent this, you can check the similarity of titles, which can be done using several methods, one of which is the Jaccard similarity algorithm, which is an algorithm that functions to find similarities or similarity of a problem, with calculations that contain a formula for solving the problem. In simple terms, this algorithm calculation will be added with a certain weighting value to increase the similarity value of the previous case with the new case. [1] Comparing title by title is very time consuming if done manually, therefore application design needs to be done so that later it can help parties. related to determining the similarity of dissertation titles. This design will later become a direction in building a dissertation title similarity detection application with the results of the title similarity percentage with the minimum acceptable level of similarity being 10%, and the consideration being 11% to 15%.